Anxiety level in severe asthmatics undergoing bronchial thermoplasty procedure: An observational study. Issue 38 (23rd September 2022) - Alismail, Abdullah; Sutzko, Kandice; Daher, Noha; Welch, Mark; Ramirez, Raul; Webb, Andrea; Tan, Laren D.
Abstract : Bronchial thermoplasty (BT) is one of the novel approved modalities in treating severe asthmatics to overcome their exacerbating symptoms such as increased anxiety. The purpose of this study was to evaluate anxiety level among severe asthmatics while undergoing BT procedure. This was an observational study where subjects self-evaluated their overall anxiety level using the burns anxiety inventory (BAI) questionnaire at baseline and prior to each of three BT treatments (broncho thermoplasty procedure 1, broncho thermoplasty procedure 2, and broncho thermoplasty procedure 3). The BAI questionnaire consisted of three different categories with each category having specific symptoms. Categories were grouped as: Anxious feelings, Anxious thoughts, and Physical symptoms. Subjects' Asthma Control Tests were also collected for analysis before and after the BT procedure. A total of 17 subjects with a mean age of 55.9 ± 14.5 years participated in the study. Fifty three percent were females (n = 9) and 41.2% (n = 7) were on prescribed anxiety medications. There was a significant drop in the patients' overall BAI anxiety level over time, P < .0001, in Anxious feelings ( P = .0001), anxious thoughts ( P = .001), and physical symptoms ( P = .025). When analyzing the change in anxiety level among those who were not on prescribed anxiety medications, significant drop in overall anxiety level and in the subcategories were also noted. ( P < .05). In addition, ACT scores showed a significant improvement (post vs pre) (18.5 ± 4.0 vs 13.3 ± 6.3, P = .03; Cohen's d = 0.73). This study shows the effectiveness of BT in decreasing severe asthmatic anxiety levels from baseline to last BT treatment and this benefit was mostly noted in those who were not on any anxiety medications. A limitation of this study is that all subjects were recruited from a single center. Therefore, to further validate the study findings, a multi-center study needs to be conducted with a larger sample size.